Mandible shape in marsupial and placental carnivorous mammals: a morphological comparative study using geometric morphometrics - Prevosti, Francisco Juan (2011)
We analysed mandible shape of the orders Dasyuromorpha, Didelphimorphia, and Carnivora using twodimensional geometric morphometrics, in order to explore the relationship between shape, size, and phylogeny. We studied 541 specimens, covering most of the genera of the terrestrial Carnivora (115 species) and a wide sample of marsupials (36 species). The observed shape variation had an ecological component. As an example, omnivorous carnivores have thick mandibles and large talonids in the carnassials, while hypercarnivores possess short mandibles and reduced talonids. There is also a discrimination between different taxonomic groups (i.e. marsupials and Carnivora), indicating some kind of constraint. Size explains a large percentage of total variance (large species had shorter and stronger mandibles, with anteriorly displaced carnassials), was significant when  phylogeny was taken into account with a comparative method, but not when size and shape were optimized on the phylogeny. Carnivora presents a larger disparity and variation in body size, which could be related to the difference in teeth replacement. The optimization of mandible shape on the phylogenetic tree indicates that functional aspects, such as diet, are a key factor in the evolution of the carnivore mandible, but also that there is a phylogenetic pattern that cannot be explained by differences in diet alone.